Gambaran Tingkat Kecemasan pada Masyarakat di Daerah Rawan Bencana Banjir di Desa Sawahan Kabupaten Klaten - Devitya Febryani Anjari Putri; Eska Dwi Prajayanti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Flood disasters frequently affect communities in vulnerable areas and may cause psychological problems, particularly anxiety. Sawahan Village, Juwiring District, Klaten Regency, is one of the flood-prone areas that experiences recurrent flooding each rainy season. Objective: This study aimed to describe the level of anxiety among people living in flood-prone areas. This quantitative descriptive study was conducted among 97 respondents selected using purposive sampling from a population of 319 residents in RT 01 and RT 02 Dukuh Bulurejo, Sawahan Village. Data were collected using the Hamilton Anxiety Rating Scale (HARS) questionnaire and analyzed through univariate analysis. Most respondents experienced mild anxiety (60.8%), followed by moderate anxiety (22.7%), no anxiety (14.4%), and severe anxiety (2.1%). The majority of people living in flood-prone areas of Sawahan Village experienced mild anxiety, indicating the presence of psychological impacts caused by repeated flood disasters while showing relatively adaptive coping abilities within the community.